2013
DOI: 10.1002/jrs.4264
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds and polymerization in acrylamide under pressure

Abstract: Acrylamide (C3H5NO), a hydrogen‐bonded amide, is an important compound from the point of view of basic and material research. It can be used as a model system for studying hydrogen bonding interactions in amides under pressure. As it is a monomer of polyacrylamide, an important polymer, high pressure investigation of polymerization in this material is also of interest. Our in‐situ high pressure Raman spectroscopic investigations of acrylamide carried out up to 17 GPa under quasi‐hydrostatic conditions indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
5
24
0
Order By: Relevance
“…The calculated infrared spectra at the MP2/aug‐cc‐pVDZ level of theory for the syn monomer and the E1 dimer, together with the di‐imidic acid structure, are compared with the experimental spectrum of Duarte et al ., as shown in Figure . A detailed spectral analysis by comparing the calculated monomer spectra with the experimental spectra had been performed in previous studies by different research groups . In particular, Singh et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated infrared spectra at the MP2/aug‐cc‐pVDZ level of theory for the syn monomer and the E1 dimer, together with the di‐imidic acid structure, are compared with the experimental spectrum of Duarte et al ., as shown in Figure . A detailed spectral analysis by comparing the calculated monomer spectra with the experimental spectra had been performed in previous studies by different research groups . In particular, Singh et al .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, acrylamide in its own right is an interesting chemical species for theoretical studies because of several reasons. First, concerning one of its possible tautomer forms, an imidic acid, previous infrared and Raman spectra 10,[16][17][18][19][20][21][22][23][24][25][26][27][28] showed no sign of the existence of such a tautomeric form. However, in condensedphase samples, the imidic acid form can be reached through a double proton transfer reaction, which could possibly compete with the monomer tautomerization.…”
Section: Introductionmentioning
confidence: 99%
“…9 The opening of C=C bonds in propene and acrylamide is also detected above 2.7 and 4 GPa, respectively. 10,11 The breakages of triple bond of the a) Electronic mail: zoubo@jlu.edu.cn ethynyl group in acetylene, cyanoacetylene, and phenylacetylene are evidenced when pressure exceeds 4.2, 1.4, and 8 GPa, respectively. [12][13][14] Hydrogen cyanide, cyanogen, and tetracyanoethylene polymerize progressively through saturating C≡N triple bonds upon compression above 1.3, 3.5, and 14 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and coworkers reported the results of Raman measurements of hydrogen bonds and polymerization in acrylamide under pressure. They found that the emergence of several new spectral features at higher pressures was indicative of the onset of polymerization …”
Section: Introductionmentioning
confidence: 92%
“…They found that the emergence of several new spectral features at higher pressures was indicative of the onset of polymerization. [241] Special Raman techniques and methods A number of papers were published that involved either speicalized instrumentation, new experimental techniques, or new methods of spectral analysis including new chemometric statistical methods for analyzing complex set of spectra.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%